Sexual Abuse, Misogyny and Hooliganism: The Perverse Logics of Troll Networks - Natarajan, Poarkodi (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Social media has been witnessing a spate of unacceptable, violating and criminal behaviours. Troll networks have been misusing Facebook and Twitter, the popular networking sites, as sites of vigilantism and mob justice. Individuals and troll armies have been unleashing terror and severe abuse on women with dissenting political opinion or questioning the patriarchal or religious order. Verbal and visual offensives targeting women’s bodies, sexualities and identities have become routine. Body shaming, revenge porn, sexting and threats of sexual violence, rape and murder threats that reeks of entrenched misogyny and sexism are harming women and online safety is emerging as a major concern. This paper analyses few specific cases of gendered online abuse to understand the nature of trolling - abuse, attacks and character assassination. The paper aims at identifying the modus operandi of troll armies and the strategies employed by women to counter the trolls and report the criminal behaviours. Further, the paper tries to trace the structure, support mechanisms and political leanings of the organized trollers. The paper also looks at the intervention of social media in situations of online abuse. How to cite this article: Natarajan P. Sexual Abuse, Misogyny and Hooliganism: The Perverse Logics of Troll Networks. J Adv Res Jour Mass Comm 2018; 5(4): 139-142.